Selected abstracts from the 2019 Simulation Summit (Advances in simulation (London), 2019)
2019 Simulation Summit/Sommet de simulation 2019 02 Material concepts: Integrating theory and practice during simulation-based training to support procedural skills retention and transfer J. J.H. Cheung1, K. M. Kulasegaram2, N. N. Woods2, R. Brydges3 1University of Toronto, Toronto, ON, Canada; 2The Wilson Centre, Toronto, ON, Canada; 3St. Michael's Hospital & University of Toronto, Toronto, ON, Canada Correspondence: J. J.H. Cheung Background: Instruction that encourages trainees to integrate conceptual “why” and procedural “how” knowledge improves their transfer of procedural skills. For training away from the bedside and direct supervision, questions remain on how to represent the causal relationship between clinical concepts and procedural actions (e.g., how patient anatomy relates to inserting a needle). Simulation presents a unique education modality for delivering causal instruction that can help trainees build cognitive connections between the theoretical concepts and procedural actions of clinical skills. We varied the modality and level of interactivity when presenting these causal relationships during simulation-based lumbar puncture (LP) training and measured impacts on participants’ retention and transfer. Research Question: When delivering integrated instruction, how does the modality (video-based or simulation-based) impact trainees’ skill retention and transfer? Methods: During a 1-hour session, we randomized 66 medical students to one of three instructional interventions: i) procedural-only video-based instruction, ii) integrated video-based instruction, and iii) integrated simulation-based instruction. One-week later, we tested participants’ LP skill retention and transfer, and their conceptual knowledge on a written test. Results: Simple mediation regression analyses revealed that participants receiving integrated instruction had superior LP retention and transfer skills via gains in conceptual knowledge (all p<0.01). We found no significant performance differences between the integrated groups (p>0.01). Participants receiving procedural-only instruction practiced significantly more LPs during training (M=2.36) than participants receiving integrated video-based (M=1.82) and simulation-based instruction (M=1.50), p<0.05. Conclusion: Trainees’ ability to create cognitive connections between conceptual and procedural knowledge appears to improve when they interact with instructional materials highlighting the causal relationships between these knowledge types. Simulation experiences can be designed to make abstract clinical concepts visible using hands-on, interactive modules, which enhances trainees’ conceptual knowledge, as well as, their skill retention and transfer. However, integrated instruction reduced participants’ time to practice LP scenarios, which may have reduced the effectiveness of our efforts to promote such “cognitive integration”. We suggest that more advanced trainees with baseline procedural proficiency may experience greater benefits from such integrated instruction. Integrated instruction may improve trainees’ skill retention and transfer, despite reducing how many LPs they could practice. 03 Does utilization of an intubation safety checklist reduce dangerous omissions during simulated resuscitation scenarios? C. Forristal1, S. Mal1, M. Columbus1, K. Van Aarsen1, D. Ouellette1, N. Farooki2, K. Hayman2, N. Smith3, S. McLeod4 1Western University, London, ON, Canada; 2University of Toronto, Toronto, ON, Canada; 3London Health Sciences Centre, London, ON, Canada; 4Scwartz/Reisman Emergency Medicine Institute, Toronto, ON, Canada Correspondence: C. Forristal Introduction: Airway management is a high-risk procedure regularly performed by emergency medicine (EM) physicians. Studies demonstrate an increase in adverse events associated with airway management outside the operating theatre, with errors of omission being the most common type of human error. To address this risk, checklists are becoming a common pre-intubation tool. Simulation is a safe setting in which to study the implementation of a new airway checklist. The purpose of this study was to determine if a novel airway checklist decreases the rate of important task omission during simulated resuscitation scenarios. Methods: This was a dual-centre, randomized controlled trial of a novel airway checklist utilized by EM practitioners in a simulated environment. The 29-item peri-intubation checklist was derived by experienced EM practitioners following a review of published airway checklists. Participants were EM residents or physicians who work more than 20 hours/month in an emergency department. Volunteers were recruited from 2 academic centres to complete 3 simulated scenarios (2 requiring intubation, 1 cricothyroidotomy), and were randomized to standard care or checklist use. A minimum of 2 assessors documented the number of omitted tasks deemed important in airway management and the time until definitive airway management. Discrepancies between assessors were resolved by single-assessor video review. Results: Fifty-four EM practitioners participated. Baseline characteristics were not significantly different between the study groups. The average percentage of omitted tasks over 3 scenarios was 45.7% in the control group (n=25) and 13.5% in the checklist group (n=29) – an absolute difference of 32.2% (95% CI: 27.8%, 36.6%). Time to intubation was significantly longer in the checklist group for the first 2 scenarios (mean difference 114.10s, 95% CI: 48.21s, 179.98s and 76.34s 95% CI: 31.35s, 121.33s), but not significantly different in the third scenario where cricothyroidotomy was required (mean difference 33.75s, 95% CI: -28.14s, 95.65s). Conclusion: In a simulated setting, use of an airway checklist significantly decreased the omission rate of important airway management tasks; however it increased the time to definitive airway management. Further study is required to determine if these findings are consistent in a clinical setting and how they impact the rate of adverse events. 04 Teaching skills via kinesthetic sensory pathway B. Zheng University of Alberta, Edmonton, AB, Canada Introduction: When learning a particular motor skill, we often acquire information through visual and kinesthetic sensory pathways. We extensively study the role of visual feedback on skill acquisition, but our knowledge on kinesthetic feedback remains rudimentary. In this study, we examined the role of kinesthetic feedback in learning laparoscopic skills. It was our hypothesis that this kinesthetic guidance received from the expert would facilitate skill learning. This was carried out as part of results from a larger project. Methods: At the Surgical Simulation Research Lab of the University of Alberta, we implemented an advance master-slave training system connecting 4 SensAble™ PHANTOM® Omni that enabled us to record an expert surgeons’ kinesthetic features from both hands and deliver those features to a surgeon-in-training while practicing a laparoscopic skill. Twelve novice medical students were asked to perform a pattern-cutting task within a laparoscopic training box. Each subject was required to perform 30 minutes per day over a six-day training phase. Six subjects in the kinesthetic-guided training group had the additional utilization of a device that allowed movement to be directly transmitted from one operator to the other, thereby allowing them to feel exactly what an expert would do under the same task. Another six subjects in the self-directed learning group received no such a feedback. Precision cutting was chosen as the surgical task due to its fidelity to real surgery and ease of analysis. Performance was evaluated by the time to completion and precision of the cut. Error analysis was completed via computer analysis of average deviations from the original line. The scores were averaged between the individuals of each group for each session and plotted over 6 sessions to yield a learning curve. Task time and cutting error duration were reduced over training phase. Results: The skill acquisition was significantly faster in the kinesthetic-guided than the self-directed training group, with decreasing amount of performance errors. Discussion: Kinesthetic feedback helps trainees to build surgical skills. Further work on correlating error analysis to video data could reveal more data regarding where and when to use haptic feedback as a future strategy to augment current and traditional surgical learning. 05 The nature of learning from simulation F. Shariff, G. Regehr, R. Hatala University of British Columbia, Vancouver, BC, Canada Correspondence: F. Shariff Background: Ongoing learning in complex clinical environments requires health professionals to assess their own performance, manage their learning, and modify their practices based on self-monitored progress. Self-regulated learning (SRL) theory suggests that while learners may be capable of such learning, they often need guidance to enact it effectively. Debriefings in simulation may be an ideal time to prepare learners for self-regulated learning in targeted areas, but may not be optimally fostering these practices. The goal of this study was to explore and characterize the nature of the learning by participants after team-based simulation training. Methods: A qualitative study informed by grounded theory methodology was conducted in the context of three Interprofessional in-situ trauma simulations at our level 1 trauma center. 18 participants were interviewed immediately, and in follow-up 4-6 weeks after the simulation experience. Transcripts were analyzed in an iterative constant comparative approach to explore emergent concepts and themes surrounding our research question. There were many examples of acquired content knowledge and straightforward practice change plans during initial interviews; however, more sophisticated examples of self-regulated learning were lacking ear